SETD2 loss of function is a recurrent event in advanced‐phase chronic myeloid leukemia and contributes to genomic instability - Manuela Mancini; Sara De Santis; Cecilia Monaldi; Fausto Castagnetti; Miriam Iezza; Alessandra Iurlo; Daniele Cattaneo; Sara Galimberti; Marco Cerrano; Isabella Capodanno; Massimiliano Bonifacio; Maura Rossi; et al. (Clinical and Translational Medicine)
Abstract The SETD2 tumour suppressor encodes a histone methyltransferase that specifically trimethylates histone H3 on lysine 36 (H3K36me3), a key histone mark implicated in the maintenance of genomic integrity among other functions. We found that SETD2 protein deficiency, mirrored by H3K36me3 deficiency, is a nearly universal event in advanced‐phase chronic myeloid leukemia (CML) patients. Similarly, K562 and KCL22 cell lines exhibited markedly reduced or undetectable SETD2/H3K36me3 levels, respectively. This resulted from altered SETD2 protein turnover rather than mutations or transcriptional downregulation, and proteasome inhibition led to the accumulation of hyper‐ubiquitinated SETD2 and to H3K36me3 rescue suggesting that a functional SETD2 protein is produced but abnormally degraded. We demonstrated that phosphorylation by Aurora‐A kinase and ubiquitination by MDM2 plays a key role in the proteasome‐mediated degradation of SETD2. Moreover, we found that SETD2 and H3K36me3 loss impinges on the activation and proficiency of homologous recombination and mismatch repair. Finally, we showed that proteasome and Aurora‐A kinase inhibitors, acting via SETD2/H3K36me3 rescue, are effective in inducing apoptosis and reducing clonogenic growth in cell lines and primary cells from advanced‐phase patients. Taken together, our results point to SETD2/H3K36me3 deficiency as a mechanism, already identified by our group in systemic mastocytosis, that is reversible, druggable, and BCR::ABL1‐independent, able to cooperate with BCR::ABL1 in driving genetic instability in CML. Key Points Virtually all CML patients in blast crisis display SETD2 loss of function. SETD2 loss seems to be accomplished at the posttranslational level rather than being the result of genetic/genomic hits or transcriptional repression. Phosphorylation by Aurora kinase A and ubiquitination by MDM2 contribute to SETD2 proteasome‐mediated degradation in blast crisis CML patients. Loss of SETD2 results in increased DNA damage.